2017
DOI: 10.3389/fnbeh.2017.00237
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Corticosterone and TrkB Pharmaco-Manipulations Sex-Dependently Impact Instrumental Reversal Learning Later in Life

Abstract: Early-life trauma can increase the risk for, and severity of, several psychiatric illnesses. These include drug use disorders, and some correlations appear to be stronger in women. Understanding the long-term consequences of developmental stressor or stress hormone exposure and possible sex differences is critically important. So-called “reversal learning” tasks are commonly used in rodents to model cognitive deficits in stress- and addiction-related illnesses in humans. Here, we exposed mice to the primary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 119 publications
(162 reference statements)
1
7
0
Order By: Relevance
“…Nevertheless, de Sousa et al (2015) report that chronic CORT exposure in female mice decreases BDNF protein levels in the PFC and induces anhedonic-like and depressive-like behavior. This pattern is consistent with our own findings that the trkB agonist 7,8-DHF can correct PFC-dependent decision-making abnormalities in CORT-exposed female adolescent mice (Barfield et al, 2017a; Barfield & Gourley, 2017b). In another report, chronic unpredictable stress decreases PFC BDNF in adult female, but not male, mice.…”
Section: Stress-induced Alterations In Pfc Trkb and Grsupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, de Sousa et al (2015) report that chronic CORT exposure in female mice decreases BDNF protein levels in the PFC and induces anhedonic-like and depressive-like behavior. This pattern is consistent with our own findings that the trkB agonist 7,8-DHF can correct PFC-dependent decision-making abnormalities in CORT-exposed female adolescent mice (Barfield et al, 2017a; Barfield & Gourley, 2017b). In another report, chronic unpredictable stress decreases PFC BDNF in adult female, but not male, mice.…”
Section: Stress-induced Alterations In Pfc Trkb and Grsupporting
confidence: 93%
“…The authors of the present review have similarly reported that oral CORT exposure in mice during early adolescence (P31–42), but not adulthood (P70–81), disrupts goal-directed decision making several weeks after the cessation of CORT (Barfield et al, 2017a). Additionally, CORT, repeated forced swimming, or trkB antagonism during the same early-adolescent period (P31–42) impairs OFC-dependent behavioral flexibility in adulthood (Barfield & Gourley, 2017b). Although studies directly comparing the long-term effects of stress or CORT during different periods of adolescence/adulthood on PFC BDNF-trkB and function are somewhat lacking, current evidence suggests that stressors during early adolescence may be more impactful than those in adulthood.…”
Section: Stress-induced Alterations In Pfc Trkb and Grmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for this hypothesis relies on epigenetic, transcriptomic and proteomic regulation of BDNF expression in rodent models and human tissues (24)(25)(26). The consensus view is that expression of BDNF and/or its receptor TrkB is diminished in the corticolimbic system (mostly prefrontal cortex and hippocampus) whereas BDNF is upregulated in the mesolimbic system (mostly nucleus accumbens, amygdala, VTA) long after cessation to stressor exposure in animal models and in postmortem human brains (27)(28)(29)(30)(31). A reduction of BDNF/TrkB signaling in the corticolimbic areas of the brain is associated with synaptic loss, decreased neuronal plasticity and regressing network connectivity, while an elevation of BDNF/TrkB signaling in the mesolimbic areas of the brain is associated with synaptic growth, increased neuronal plasticity and expanding network connectivity (32)(33)(34)(35)(36)(37).…”
Section: Brain Region-specific Effects Of Bdnf and Glucocorticoids Onmentioning
confidence: 99%
“…It has been reported that chronic glucocorticoid treatment disrupts the interaction between glucocorticoid receptors and TrkB with subsequent dampening of the PLCγ signaling pathway (Numakawa et al, 2013 ), with implications for cognition. Yan et al ( 2016 ) recently demonstrated that chronic CORT treatment decreased pTrkB, and Barfield and Gourley ( 2017 ) showed truncated TrkB, the inactive form, to be increased in relation to FL-TrkB after chronic adolescent CORT treatment. Our study adds to this literature by investigating the activation of the distinct residues, and the results discussed above contribute to creating a comprehensive molecular map of how glucocorticoids and the BDNF-TrkB signaling pathway dynamically interact.…”
Section: Discussionmentioning
confidence: 99%